PENGARUH CONTENT MARKETING, E-MAIL MARKETING DAN MOBILE MARKETING TERHADAP CUSTOMER ENGAGEMENT PADA NADIA MART DAWAS - Ida Bagus Kurniawan; Natalia Sri Endah Kurniawati; I Wayan Ruspendi Junaedi (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
Nadia Mart Dawas is one of the UMKM in Badung that uses digital marketing for promoting the product. The types of digital marketing that used is Content Marketing, E-Mail Marketing and Mobile Marketing. The Digital marketing efforts are closely related to customer engagement. Customer engagement is a behavior that makes customers contribute to the company's where the contribution is not only like the purchase of the product but the contribution given is a feedback, suggestions and ideas. This research was conducted with the aim of knowing the effect of Content Marketing, E-Mail Marketing and Mobile Marketing on Customer Engagement at Nadia Mart Dawas. This research was conducted by distributing online questionnaires to 150 respondents who are customer of Nadia Mart Dawas. The method used in this study is multiple linear regression to determine the effect of several variables on other variables. Based on the research that has been done, the results show that content marketing variables, email marketing variables and mobile marketing variables partially have a significant effect on customer engagement, and after all the variables X tested together has an effect on variable Y with a percentage of influence are 55.5% , and 45.5% is influenced by variables that are not used in this study.